2010
DOI: 10.1016/j.jmedhist.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Henry I's dream in John of Worcester's Chronicle (Oxford, Corpus Christi College, MS 157) and the illustration of twelfth-century English chronicles

Abstract: Keywords:Chronicle illumination John of Worcester Henry of Huntingdon Dreams of Henry I of England Sun spots Crucifixion Diagrams a b s t r a c t Henry I's four-part dream sequence in John of Worcester's Chronicle is well known to both historians and art historians as a rare but striking historical illustration. This article examines the location of the images within the manuscript itself as well as in the broader context of twelfth-century chronicle illustration. Despite the flourishing of history writing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Like Michael Kauffmann somewhat earlier, Collard concluded that chronicle illustration was a rarity before the thirteenth century. 48 Only the chronicle of St Martin des Champs (now B.L. Ms Add.…”
mentioning
confidence: 99%
“…Like Michael Kauffmann somewhat earlier, Collard concluded that chronicle illustration was a rarity before the thirteenth century. 48 Only the chronicle of St Martin des Champs (now B.L. Ms Add.…”
mentioning
confidence: 99%